2021
DOI: 10.1111/1440-1681.13492
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic analysis of ropivacaine extended‐release from a temperature‐responsive hydrogel in rats

Abstract: Therapeutic agents with a short half‐life need to be administered frequently to achieve sustained and effective concentrations. This could be accomplished using sustained drug delivery technology. PF‐72 (TGel Bio, Inc., Seoul, Korea) is a drug delivery system based on a powder obtained from lyophilisation of a reverse thermal hydrogel, which could assist in achieving prolonged pain relief if mixed with an anaesthetic and injected into the incision site following surgery. The pharmacokinetic parameters related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Bang JY, et al performed an animal experiment to assess the population pharmacokinetic profile of 0.75% ropivacaine combined with PF-72, thus showing that there was an increase in the duration of absorption in the blood. These authors suggested that PF-72 combined with 0.75% ropivacaine might sustain effects of 0.75% ropivacaine at the surgical site [14]. Moreover, Oh KS, et al conducted a preclinical study to assess the pharmacokinetic, distribution and efficacy of PF-72 containing 0.75% ropivacaine for extended relief of postoperative pain by allowing the prolonged release of ropivacaine.…”
Section: Introductionmentioning
confidence: 99%
“…Bang JY, et al performed an animal experiment to assess the population pharmacokinetic profile of 0.75% ropivacaine combined with PF-72, thus showing that there was an increase in the duration of absorption in the blood. These authors suggested that PF-72 combined with 0.75% ropivacaine might sustain effects of 0.75% ropivacaine at the surgical site [14]. Moreover, Oh KS, et al conducted a preclinical study to assess the pharmacokinetic, distribution and efficacy of PF-72 containing 0.75% ropivacaine for extended relief of postoperative pain by allowing the prolonged release of ropivacaine.…”
Section: Introductionmentioning
confidence: 99%